From Third World to First : Singapore and the Asian Economic Boom - Lee, Kuan Yew (New York Harper Collins Publishers, 2011)
"Few gave tiny Singapore much chance of survival when it was granted independence in 1965. How is it, then, that today the former British colonial trading post is a thriving Asian metropolis?" "The story of that transformation is told here by Lee Kuan Yew. Rising from a legacy of divisive colonialism, the devastation of the Second World War, and general poverty and disorder following the withdrawal of foreign forces, Singapore now is hailed as a city of the future. This history is recounted by the man who not only lived through it all but who forged ahead and brought about most of these changes." "Delving into his own notes, as well as previously unpublished government papers and official records, Lee details the extraordinary efforts it took for an island city-state in Southeast Asia to survive at that time."--Jacket.
Include Illustrations and Index